The Influence of Competence on Performance Employees Mediated with Quality of Work Life - Vivi Nasya Laela; Zulkifli (Optima Science, 2024)
Employee performance is one of the factors that is very influential in the work system, whether an organization or institution, and whether an agency is good or not can be seen from how well its employees perform. To avoid the bad side of employee performance, adequate competency and Quality of Work Life is needed, so that it can improve the quality and more optimal performance of an organization. This research aims to identify the effect of Competency on Employee Performance through strengthening the Quality of Work Life (for Widyagama University Malang Employees). The issue raised in this research is improving the performance of employees who are felt to have not achieved perfect grades. The population in this study were 73 permanent employees who worked at Widyagama University Malang. Data is processed using the Smart Partial Square (PLS) software application. The research results show that good competency can improve employee performance. Good competencies can improve the quality of work life. Good quality of work life can improve employee performance. Good competencies can improve employee performance through quality of work life.